Knowledge, attitude, and practice of oral nutritional supplements in patients undergoing radiotherapy for head-and-neck cancer - Chen, Yajun; Yang, Shuang; Li, Yuying; Li, Chunlei; Chen, Mengyuan; Wang, Ruina; Liu, Na; Fang, Yu; Han, Mingming; Tang, Hongwei; Zhang, Jun; Zeng, Yaqi; et al. (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to explore the knowledge, attitude, and practice (KAP) of oral nutritional supplementation in patients undergoing radiotherapy for head-and-neck cancer.Materials and methodsA multicenter cross-sectional study was conducted from December 2023 to July 2024 across five medical institutes. Demographic data and KAP scores were collected and assessed using a self-developed validated questionnaire. A threshold of ≥70.0% of the maximal scores was established to define good knowledge, a positive attitude, and active practice.ResultsA total of 437 valid questionnaires were analyzed; the majority of participants were men (70.71%) and aged between 41 and 60 years (50.11%). The median knowledge score was 4 (range: 0–10; possible range: 0–20), the median attitude score was 34 (range: 30–39; possible range: 10–50), and the median practice score was 15 (range: 13–17; possible range: 4–20). The knowledge score exhibited a positive correlation between both attitude (r = 0.379, p < 0.001) and practice (r = 0.395, p < 0.001) scores; attitude and practice scores were also positively correlated (r = 0.363, p < 0.001). Structural equation modeling showed that knowledge had a direct positive effect on attitude (β = 0.613, p < 0.001) and practice (β = 0.807, p < 0.001), while attitude had a direct effect on practice (β = 0.614, p < 0.001).ConclusionThe findings indicate that patients with head-and-neck cancer undergoing radiotherapy exhibit poor knowledge and unfavorable attitudes toward oral nutritional supplements, despite displaying proactive practices. Considering the positive correlation among KAP, the provision of personalized medical education is essential for effective disease management.